Kenya scaling week - Ewell, Hanna; Nzuki, Esther (2024)
The AICCRA Kenya Scaling Week workshop, held at ILRI Campus from October 28th to 29th 2024, focused on advancing the responsible and inclusive scaling of Climate Information Services (CIS) and Climate-Smart Agriculture (CSA) solutions to enhance resilience among smallholder farmers in Kenya. The workshop explored diverse scaling approaches and introduced the AICCRA Scaling Framework, focusing on effective demand, technical excellence, and sustained use of climate-smart solutions.